Growth crisis or absence of infrastructures (2003)
This article tries to advance as in the formulation of some pertinent questions, as in the suggesting of an initial interpretation as a way of work hypothesis. It also considers that the fundamental base of all civilization is in the appropriate construction of its infrastructures. These are high-priority for the sustainability of the life conditions in urban areas, independent of their degree of development and indispensable for the suitable extension of their urban growth. By this way is suggested as work hypothesis the Bogota city that during XIX century did not count with appropriate infrastructures for its growth, nor with the collective dowries that could maintain a vegetative increase of their population in relatively constant conditions.